Non-contraceptive benefits of oral contraceptives - Dhont M (Dove Medical Press, 2011)
Marc Dhont Department of Obstetrics and Gynecology, Ghent University Hospital, Ghent, Belgium Abstract: The health benefits of the oral contraceptive (OC) pill are numerous and outweigh the risks of OC use. There are unintended but useful preventive side effects and potential therapeutic uses of OCs apart from contraception itself. Unequivocal evidence for the protective influence of combined OCs against ovarian and endometrial cancers, and colon cancer to a lesser extent, has been found. The pill also reduces the incidence of benign breast disease, functional ovarian cysts, pelvic inflammatory disease requiring hospitalization, ectopic pregnancy, and iron-deficiency anemia. The pill can be used for the treatment of several gynecologic disorders such as dysmenorrhea, irregular or excessive bleeding, acne, hirsutism, and endometriosis-associated pain, whether prescribed solely to treat these symptoms or prescribed to treat them in addition to providing contraception. These health benefits are often underestimated, as they get too little attention from the mass media. Keywords: the pill, estrogens, progestogens, safety, contraception